2019
DOI: 10.3390/nu11030490
|View full text |Cite
|
Sign up to set email alerts
|

The Type of Dietary Fat in an Isocaloric Breakfast Meal Does Not Modify Postprandial Metabolism in Overweight/Obese Pregnant Women

Abstract: Almonds provide a satiating, healthy source of fat and fiber. The postprandial metabolic and satiety response to 2 ounces of nuts or dairy was assessed in 18 overweight/obese women during late pregnancy. Serum glucose, triglycerides, insulin, c-peptide, leptin, ghrelin, and lipoprotein particles were measured prior to and during a 5-h postprandial period following the consumption of an isocaloric breakfast meal with equivalent amounts of fat from either nuts or dairy on two separate mornings. Satiety was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In agreement with our findings, Lesser et al examined the lipemic effects of a mixed breakfast meal with the fat derived from almonds (MUFA) or cream cheese (dairy-based SFA) in overweight/obese pregnant women and found no significant difference in the postprandial TG response between the two meal trials (MUFA versus dairy-based SFA) [28]. Notably, the test meal utilized by Lesser et al [28] was a mixed meal, containing a heterogeneous mixture of macro- and micronutrients. Likewise, the HFM meal used in the present study contained moderate amounts of CHO (32% of total kcal) derived from fiber-rich whole grains, French bread, and vegetables.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our findings, Lesser et al examined the lipemic effects of a mixed breakfast meal with the fat derived from almonds (MUFA) or cream cheese (dairy-based SFA) in overweight/obese pregnant women and found no significant difference in the postprandial TG response between the two meal trials (MUFA versus dairy-based SFA) [28]. Notably, the test meal utilized by Lesser et al [28] was a mixed meal, containing a heterogeneous mixture of macro- and micronutrients. Likewise, the HFM meal used in the present study contained moderate amounts of CHO (32% of total kcal) derived from fiber-rich whole grains, French bread, and vegetables.…”
Section: Discussionsupporting
confidence: 91%
“…As part of a mixed meal, fiber has been shown to blunt the PPL response by interfering with lipid absorption and digestion via impairment of proper emulsification of lipids in the gastrointestinal tract [29]. In support of this concept, Lesser et al utilized a mixed meal consisting of 46% of calories derived from CHO and found no differences between test meals [28]. The almond test meal contained 7 g more fiber when compared to the cream cheese test meal; therefore, the lack of detectable differences between meals may have been a result of the modifying effect of fiber on PPL.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more and more people are paying attention to healthy eating. This phenomenon is linked to the increasing awareness of consumers about environmental and health issues [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…A three day crossover of isocaloric high carbohydrate/low-fat diet (60%CHO/25%fat/15%protein) compared to low carbohydrate/high-fat diet (40% CHO/45%fat/15% protein) in 16 women found no difference in serum triglyceride incremental AUC but lower serum free fatty acids in the high carbohydrate/low-fat diet after breakfast on day 4 of the diet [ 19 ]. An isocaloric breakfast meal with equivalent macronutrient composition but different types of fat intake in 18 women in late pregnancy did not report any alterations in the postprandial serum triglyceride levels [ 20 ]. Both of these studies attempted to control for overall diet and medication use before and during the meal, but in the setting of a less dramatic difference in dietary composition compared to the studies outside pregnancy described in the above paragraph, no difference in triglycerides was seen.…”
Section: Discussionmentioning
confidence: 99%